Characteristics of Circumstances and Influential Forces of Migration in Nepal (1990-2016): An Integrative Literature Review - Ghimire, Narayan; Hillman, Wendy (Journal of Development and Social Engineering, 2022)
The aftermath of conflicts and better livelihood as well as financial opportunities are the main push-pull factors of migration in Nepal. The authors surveyed several articles published between 1990 and 2016, which feature the various dimensions of both internal and international migration in Nepal such as; the context of migration, challenges of acculturation, and also forms of migration other than labor migration. This integrative literature review was undertaken in order to explore the inherent characteristics of both internal as well as international migration in Nepal. We found that a lack of employment opportunity in their home country caused a significant rise in the international migration from Nepal, mainly to Gulf countries. Besides that, the review also explores the factors of better livelihood opportunities in urban areas and the impact of conflicts as potential reasons of internal migration in Nepal. This research disseminates awareness of the inherent factors of both internal and international migration patterns in Nepal which will be supportive to the concerned government authorities in systematizing new migration policies.